A Congruence Relation in Partially Ordered Sets: C. Ganesamoorthy, SG. Karpagavalli - Team, Support (Thai Journal of Mathematics, 2015)
A concept of congruence relations in partially ordered sets is introduced in this article. A fundamental theorem for homomorphism is obtained. Further extensions to “doubly directed” sets are obtained.